2016
DOI: 10.1002/oby.21448
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle and plasma lipidomic signatures of insulin resistance and overweight/obesity in humans

Abstract: Objective: Alterations in lipids in muscle and plasma have been documented in insulin-resistant people with obesity. Whether these lipid alterations are a reflection of insulin resistance or obesity remains unclear. Methods: Nondiabetic sedentary individuals not treated with lipid-lowering medications were studied (n 5 51). Subjects with body mass index (BMI) > 25 kg/m 2 (n 5 28) were stratified based on median glucose infusion rate during a hyperinsulinemic-euglycemic clamp into insulin-sensitive and insulin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
116
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 40 publications
18
116
0
Order By: Relevance
“…In a study investigating insulin resistance in humans, it was shown that, in muscle, Cer(d18:1/18:0) was the only lipid elevated by insulin resistance independently of obesity, and in plasma, Cer(d18:1/18:0), together with its precursor Cer(d18:0/18:0), was associated with both insulin resistance and obesity [24]. The same study also demonstrated that there was a positive correlation between plasma and muscle concentrations of Cer(d18:1/18:0), and this lipid correlated positively with visceral and liver fat and inversely with metabolic flexibility, which was determined by the change in respiratory quotient at rest and after insulin stimulation [24]. Another study supports these findings by showing that the concentration of Cer(d18:1/18:0) was significantly higher in type 2 diabetic individuals than athletes, and it was positively associated with BMI and inversely associated with insulin sensitivity [25].…”
Section: Discussionmentioning
confidence: 99%
“…In a study investigating insulin resistance in humans, it was shown that, in muscle, Cer(d18:1/18:0) was the only lipid elevated by insulin resistance independently of obesity, and in plasma, Cer(d18:1/18:0), together with its precursor Cer(d18:0/18:0), was associated with both insulin resistance and obesity [24]. The same study also demonstrated that there was a positive correlation between plasma and muscle concentrations of Cer(d18:1/18:0), and this lipid correlated positively with visceral and liver fat and inversely with metabolic flexibility, which was determined by the change in respiratory quotient at rest and after insulin stimulation [24]. Another study supports these findings by showing that the concentration of Cer(d18:1/18:0) was significantly higher in type 2 diabetic individuals than athletes, and it was positively associated with BMI and inversely associated with insulin sensitivity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other C18:0 sphingolipids (dihydroceramide and glucosylceramide) have been associated with insulin resistance (Bergman et al, 2016). The association between C18:0 ceramides and insulin resistance was extended by a study showing associations between insulin resistance and ceramide di18:1/18:0 and C18:0 sphingolipids dihexosylceramide and trihexosylceramide (Tonks et al, 2016). Furthermore, ceramides C14:0, C16:0 and C18:0 were increased in obese insulin-resistant women compared with those of obese insulinsensitive women (Coen et al, 2010).…”
Section: Ceramidesmentioning
confidence: 99%
“…Furthermore, as most lipid species are non-volatile and tend to degrade at high temperatures used in GC, liquid chromatography (LC) systems, coupled to MS detection emerged as powerful tools in lipidomics applications [35,36]. Besides commonly used high performance liquid chromatography (HPLC) systems with normal and reverse phase columns, UHPLC (ultra high performance chromatography), operating at pressures up to 15,000 psi now provide better mass resolution, enhanced sensitivity and greater signal-to-noise ratio [37,38,39]. The chromatographic separation of lipid species reduces ion suppression by reducing the number of competing analytes, entering the MS system at the same time.…”
Section: Analytical Approaches To Study Lipidsmentioning
confidence: 99%